Perbandingan Pendapatan Usahatani Padi Varietas Ciherang dan Mekongga di Desa Rogomulyo - Marsela Anggita Ratri; Yuliawati Yuliawati (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2019)
The purpose of this research is to (1) analyze the differences in rice farming of Ciherang and Mekongga varieties, (2) to determine R/C ratio of rice farming in Ciherang and Mekongga varieties, (3) to determine the factors that influence the differences of income in rice farming between Ciherang and Mekongga varieties. This study carried out at Rogomulyo village, Kaliwungu, Semarang. Allegedly factors that affecting the differences income are seed costs, pesticide costs, fertilizer costs, labor costs, grain prices, land area and dummy varieties. The number of farmers who planted Ciherang varieties was 211 people and the number of farmers who planted Mekongga varieties was 158 people. Simple random sampling technique with a sample of 40 Ciherang varieties and 40 Mekongga rice farmers. Data collection is done through interview using questionnaires. Analysis of the data used inclued analysis of unpaired t-test (independent sample t-test), R/C ratio, and multiple linier regression. The results showed that the difference in income of rice farmers of Ciherang and Mekongga varieties was Rp 1.507,056/Ha/planting season but statistically different. The R/C ratio of Ciherang variety rice farming is 2,39 while the R/C ratio of Mekongga varieties is 1,79. Factors that influence income differences are fertilizer costs, labor costs, grain prices, grain prices, land area and production while aeed costs, pesticidae costs, dummy varities have no effect.  Keywords : Ciherang R/C ratio, Mekongga R/C ratio, Income difference, Rice farming.